2021
DOI: 10.3390/pharmaceutics13122150
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Optimization of Garlic Oil/Apple Cider Vinegar Nanoemulsion Loaded with Minoxidil to Treat Alopecia

Abstract: Alopecia areata is a scarless, localized hair loss disorder that is typically treated with topical formulations that ultimately only further irritate the condition. Hence, the goal of this study was to develop a nanoemulsion with a base of garlic oil (GO) and apple cider vinegar (APCV) and loaded with minoxidil (MX) in order to enhance drug solubilization and permeation through skin. A distance coordinate exchange quadratic mixture design was used to optimize the proposed nanoemulsion. Span 20 and Tween 20 mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…The in-vitro dissolution results indicated that 50% of the ZP dose loaded in the optimized ZP-LV-SNELTs formulation was released in simulated saliva fluid with a pH of 6.8 within 45 sec compared with the commercial conventional tablet formulation, which released the same drug amount (50%) after 13 min. The enhancement in ZP release from the developed optimal formulations signified the improvement of ZP dissolution in the nanosized drug delivery system, which offered a large surface area for drug dissolution and release (Rizg et al., 2021 ). Figure 7 shows the in-vitro drug release profiles of the optimized ZP-LV-SNELTs versus the commercial formulation.…”
Section: Resultsmentioning
confidence: 99%
“…The in-vitro dissolution results indicated that 50% of the ZP dose loaded in the optimized ZP-LV-SNELTs formulation was released in simulated saliva fluid with a pH of 6.8 within 45 sec compared with the commercial conventional tablet formulation, which released the same drug amount (50%) after 13 min. The enhancement in ZP release from the developed optimal formulations signified the improvement of ZP dissolution in the nanosized drug delivery system, which offered a large surface area for drug dissolution and release (Rizg et al., 2021 ). Figure 7 shows the in-vitro drug release profiles of the optimized ZP-LV-SNELTs versus the commercial formulation.…”
Section: Resultsmentioning
confidence: 99%
“…A visual examination was done of the rapid emulsification capacity and transparency of the ALS-NEs to assess the NE competency (Rizg et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The targeted samples were subjected to the dynamic light-scattering method (Zetatrac, Microtrac, Montgomeryville, PA, USA) in order to quantify the size of the NEs’ droplets and the NEs’ polydispersity indexes (PDIs). Assessments were done in triplicate (Rizg et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations